Wild olive seed weevil, Anchonocranus oleae Marshall (Coleoptera: Curculionidae), in cultivated olives in South Africa - Allsopp, Elleunorah; Knipe, Muriel C; van Asch, Barbara; Caleca, Virgilio (African Entomology, 2023)
Wild olive seed weevil, Anchonocranus oleae Marshall, larvae as well as oviposition and feeding damage were recorded in cultivated olives during a recent study on olive seed wasps. Prematurely dropped fruit and fruit picked at harvest in two orchards near Stellenbosch and Agter-Paarl were examined regularly for olive seed wasp infestation over three seasons. In addition, olives were collected in the olive growing regions of the Western Cape province for a survey to determine olive seed wasp distribution. DNA barcoding was used to confirm the identity of weevil larvae in kernels. The number of A. oleae larvae found in olive seeds and the number of olives with weevil oviposition or feeding damage in this study were low. The presence of larvae and weevil damage in two orchards in the survey with no wild olive trees in close proximity suggest that the weevil could breed and persist in cultivated olive orchards. Currently A. oleae is not of economic concern, but if infested olives are discarded at harvest and left in orchards, the weevils could complete their development in the kernels and numbers could eventually increase to damaging levels.